(untitled) (Jurnal Bahasa, 2005)
This paper discusses the grammatical relation between a meN-kan transitive word and its object. Renowned Malay grammarians such as Za iba (1965), Asmah Hj. Omar (1993) and Nik Safiah Karim et al. (1997) agree that every transitive word must be followed by an object. Asraf (1989) strongly claimed that the transitive word and its object cannot be separated or intervened by any element be-cause the transitive verb phrase is a bound structure. In contrary, this paper attempts to argue and demonstrate that there are certain elements, which can separate the transitive verb and its object. Based on a data-based corpus, it is observed that at least there are two elements, which can break up the verb and its objects, namely a preposition and an adverb word. This in turn generates the following structures: Transitive Verb + Preposition + Object and Transitive Verb + Adverb Word + Object in Malay. In order to explain the behaviour of these structures, we use an eclectic approach by adopt-ing the theoretical framework of Relevances and Transformational Grammar.